Design of LQR and LQT Controls on DC Motors to Improve Energy Efficiency in Community Service Programs - Fortunaviaza Habib Ainudin; Anggara Trisna Nugraha (Politeknik Perkapalan Negeri Surabaya, 2024)
The effectiveness and efficiency of motor speed control are critical for sustainable development, particularly in community-based industries. A control system, defined as a mechanism to regulate, command, and manage a system's state, plays a significant role in optimizing energy usage. DC motors, widely utilized for their linear torque-speed characteristics and high efficiency, are preferred due to their simple control systems and minimal hardware requirements. This research focuses on developing and implementing Linear Quadratic Regulator (LQR) and Linear Quadratic Tracking (LQT) control systems for DC motors, particularly in community service programs aimed at improving energy efficiency in small-scale industries or maritime applications. The study was conducted in several stages, starting with a comprehensive literature review on first-order mathematical modeling, LQR, and LQT methodologies using journal articles, papers, videos, and books. Subsequently, DC motor specifications were obtained from datasheets and converted into first-order mathematical models. The LQR formulation was applied to derive state-space models through MATLAB programming. Experimental results demonstrate that LQR and LQT controls significantly enhance motor speed optimization while minimizing input signals. However, the introduction of noise or disturbances in the system caused instability, resulting in non-uniform motor speed. The study highlights the potential of LQR and LQT controls to improve energy efficiency in DC motor applications within community service programs. These findings can benefit communities by reducing operational energy costs and supporting sustainable technology adoption.